2020
DOI: 10.3389/fphar.2020.01196
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Therapeutic Options Under Investigation

Abstract: Since its emergence in China in December 2019, COVID-19 has quickly spread around the globe causing a pandemic. Vaccination or the development of herd immunity seems the only way to slow down the spread of the virus; however, both are not achievable in the near future. Therefore, effective treatments to mitigate the burden of this pandemic and reduce mortality rates are urgently needed. Preclinical and clinical studies of potential antiviral and immunomodulatory compounds and molecules to identify safe and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 295 publications
(338 reference statements)
0
85
0
Order By: Relevance
“…C-4 have completed their randomized clinical trials as potential inhibitors of 6LU7 (Kaddoura et al 2020 ), suggesting that they are allosteric inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C-4 have completed their randomized clinical trials as potential inhibitors of 6LU7 (Kaddoura et al 2020 ), suggesting that they are allosteric inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The sources, species name, and biological activities of the studied compounds are shown in Table 1 . Also, three standards (Remdesivir, Dexamethasone, and N3 inhibitor) whose completed randomized trials and inhibitory activities against the novel SARS-CoV-2 (M pro ) have been reported (Kaddoura et al 2020 ; Jin et al 2020 ) were used for comparison. The Saponins/Tannins used are Priverogenin A, Arjunic acid, Theasapogenol B, Euscaphic Acid, Camelliagenin C, Medicagenic Acid, Protoescigenin, Arjunolic acid, Asiatic acid, Protobassic acid, Arjugenin, Polygalacic acid, Primulagenin A, Soyasapogenol B, Tomentosic acid, Presenegenin, Punicalagin, Punicalin, Ellagic acid, Corilagin, Gallagic acid, Terflavin B. Catechin, Chebulinic acid, Hexahydroxydiphenic acid, Gallic acid, and Catechol respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, the authors reported that antivirals targeting RdRp of other viruses (HCV, MERS and SARS) such as sofosbuvir and remdesivir could bind and stop the activity of this protein. A recent clinical trial did not confirm the activity of remdesivir against SARS-CoV-2 [ 110 ] but other studies suggested that this drug can shorten the time to recovery in some patients [ 111 ]. On this basis, FDA issued an emergency use authorization for remdesivir for the treatment of COVID-19 patients hospitalized with severe disease.…”
Section: Drug-repurposing Strategies For Covid-19mentioning
confidence: 99%
“…Furthermore, monoclonal antibodies reduced inflammation by inhibiting FcR stimulation. Nevertheless, these therapies have some vulnerabilities such as abnormal reactions, short-term safety, toxins, and dissemination of causative agents ( 107 , 108 ).…”
Section: Control and Prevention Of Sars-cov-2mentioning
confidence: 99%